QHILAZ: AN ALTERNATIVE MICRO FINANCING MODELS FOR LABORER FISHER IN WEST JAVA INDONESIA - Kurnia, Tuti -; Alhifni, Anas - (JURNAL SYARIKAH : JURNAL EKONOMI ISLAM, 2019)
The purpose of this study is to find out an alternative for micro finance model for labor fishers in west Java Indonesia. This study was conducted using a qualitative approach. The data analysis technique used is ANP (Analytic Network Processing). The results of the study showed that the model that can be applied to labor fishers in west Java Indonesia is the QHILAZ model, which is a financing model for labor fishers using the qardhul hasan agreement that combines cooperation between Islamic Microfinance Institution, Amil Zakat institutions and the government.